2015
DOI: 10.1128/jcm.02932-14
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Species-Level Identification of Clinical Isolates of Coagulase-Negative Staphylococci: Does It Change the Perspective on Staphylococcus lugdunensis?

Abstract: Unbiased species-level identification of coagulase-negative staphylococci (CoNS) using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) identified Staphylococcus lugdunensis to be a more commonly isolated CoNS in our laboratory than previously observed. It has also highlighted the possibility of vertical transmission. C oagulase-negative staphylococci (CoNS) have been mostly considered insignificant contaminants when isolated from clinical samples. This, in turn, has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The widespread adoption of MALDI-TOF MS for bacterial identification has allowed clinical laboratories to better identify staphylococci to the species level (6,38). Rapid adoption of this technology, combined with an increasing immunocompromised population and close contact between humans and companion animals, has increased the number and diversity of clinically significant CoNS isolates identified (39). This increase leads to the issue of determining which methods are best for detecting mecA-mediated oxacillin resistance in CoNS, which has not been critically evaluated for many species.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread adoption of MALDI-TOF MS for bacterial identification has allowed clinical laboratories to better identify staphylococci to the species level (6,38). Rapid adoption of this technology, combined with an increasing immunocompromised population and close contact between humans and companion animals, has increased the number and diversity of clinically significant CoNS isolates identified (39). This increase leads to the issue of determining which methods are best for detecting mecA-mediated oxacillin resistance in CoNS, which has not been critically evaluated for many species.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a retrospective study, Elamin et al (29) showed that implementation of MALDI-TOF MS in 2010 for routine diagnostic use allowed the identification of 559 S. lugdunensis strains among 20,806 CoNS during a 24-month period, whereas 31 isolates were identified in the preceding 24 months using conventional methods (29). They also performed a clinical analysis for 478 individual isolates of S. lugdunensis and found no infectious diagnosis for 80 strains (16.7%), wound infection for 124 strains (25.9%), 99 abscesses (20.7%), and 12 significant bacteremias (2.5%), with 2 endocarditis cases (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason these species have often been misidentified as S. aureus in the clinic, leading to an under appreciation of their contribution to disease (Argemi et al, 2015; Elamin et al, 2015). S. lugdunensis is particularly virulent among CoNS species, and can cause a range of invasive infections, including endocarditis, sepsis, abscesses and wound infections (Frank et al, 2008).…”
Section: Fibrinogen/fibrin Mediated Clumpingmentioning
confidence: 99%